2022
DOI: 10.1002/prot.26448
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of heparin derivatives with recombinant human keratinocyte growth factor: Structural stability and bioactivity effect study

Abstract: Heparin and heparan sulfate are important glycosaminoglycans that can regulate the activities of many vital proteins, especially the fibroblast growth factor (FGF) family.Because FGF7 (KGF) has an important role in tissue repair and maintaining the integrity of the mucosal barrier, recombinant human keratinocyte growth factor (rhKGF, palifermin) has been approved for the treatment of wound healing and oral cavity.Due to heparin plays an important role in the KGF signaling pathway, a more detailed study of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…By analyzing the first three principal components (PC1, PC2, and PC3) that account for the most variance in the original data (i.e. the largest uncorrelated motion in the trajectory) 44 of tp1 and the four other systems, we observed that ZINC000014708292 accounted for higher variances of 56.2% for the total of the first three PCs, indicating that this ligand increased the motion of the protein’s Cα-atoms, 45 followed by ZINC000014819517, which showed a variance of 48.7%. ZINC000001580795 and ZINC000004098719 exhibited a variance of 36.1% and 36.7%, respectively, meaning that these two ligands induced more stable movement of the protein’s Cα atoms than TP1, which showed a variance of 33.9% for the total of the first three PCs.…”
Section: Resultsmentioning
confidence: 98%
“…By analyzing the first three principal components (PC1, PC2, and PC3) that account for the most variance in the original data (i.e. the largest uncorrelated motion in the trajectory) 44 of tp1 and the four other systems, we observed that ZINC000014708292 accounted for higher variances of 56.2% for the total of the first three PCs, indicating that this ligand increased the motion of the protein’s Cα-atoms, 45 followed by ZINC000014819517, which showed a variance of 48.7%. ZINC000001580795 and ZINC000004098719 exhibited a variance of 36.1% and 36.7%, respectively, meaning that these two ligands induced more stable movement of the protein’s Cα atoms than TP1, which showed a variance of 33.9% for the total of the first three PCs.…”
Section: Resultsmentioning
confidence: 98%